Two new species of Pelagodes Holloway, 1996 from Eastern New Guinea (Lepidoptera: Geometridae, Geometrinae, Thalassodini) - Aare Lindt; Lennart Lennuk; Jaan Viidalepp (SHILAP)
Two new species of the Indo-Australian genus Pelagodes Holloway, 1996 are described as new. Pelagodes sebastiani Lindt, Lennuk & Viidalepp, sp. nov. resembles Pelagodes rana Holloway, 1996 in the shape of its frog-leglike appendages on the male eighth abdominal sternite. The appendages are strongly curved in P. rana, while almost straight in P. sebastiani Lindt, Lennuk & Viidalepp, sp. nov. The second newly described species, Pelagodes tristani Lindt, Lennuk & Viidalepp, sp. nov., somewhat resembles Pelagodes furcatus Inoue, 2006 but differs in many aspects in the ornamentation of the male genitalia. The adults and their male genitalia structures are described and illustrated. It is noteworthy that both Papuan species of Pelagodes share massive processes on their eight sternites.